2010
DOI: 10.1007/bf03217567
|View full text |Cite
|
Sign up to set email alerts
|

University students’ difficulties in solving application problems in calculus: Student perspectives

Abstract: This paper reports on the results of an observational parallel study conducted simultaneously at 2 universities -one each in New Zealand and Germany. It deals with university engineering students' difficulties in the formulation step of solving a typical application problem from a first-year calculus course. Two groups of students (54 in New Zealand and 50 in Germany) completed a questionnaire about their difficulties in solving the problem which was set as part of a mid-semester test. The research endeavoured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 17 publications
0
16
1
1
Order By: Relevance
“…Research has shown that in the first stage students often misunderstand the meaning of the tasks and misinterpret the terms used in the tasks (Bernardo, 1999;Klymchuk, Zverkova, Gruenwald, & Sauerbier, 2010). In the second stage, students struggle with identifying the mathematical concept or procedure that is needed to solve the tasks (Clements, 1980;Klymchuk et al, 2010).…”
Section: Stages In Students' Reasoning When Solving Context-based Tasksmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown that in the first stage students often misunderstand the meaning of the tasks and misinterpret the terms used in the tasks (Bernardo, 1999;Klymchuk, Zverkova, Gruenwald, & Sauerbier, 2010). In the second stage, students struggle with identifying the mathematical concept or procedure that is needed to solve the tasks (Clements, 1980;Klymchuk et al, 2010).…”
Section: Stages In Students' Reasoning When Solving Context-based Tasksmentioning
confidence: 99%
“…Research has shown that in the first stage students often misunderstand the meaning of the tasks and misinterpret the terms used in the tasks (Bernardo, 1999;Klymchuk, Zverkova, Gruenwald, & Sauerbier, 2010). In the second stage, students struggle with identifying the mathematical concept or procedure that is needed to solve the tasks (Clements, 1980;Klymchuk et al, 2010). This difficulty relates to students' tendency either to ignore the context and try to apply a routine mathematical procedure without realistic considerations (Blum, 2015;Verschaffel, Greer, & De Corte, 2000;Xin, Lin, Zhang, & Yan, 2007) or to take too much account of the context of the tasks so that no mathematical concept or procedure is used (Boaler, 1994).…”
Section: Stages In Students' Reasoning When Solving Context-based Tasksmentioning
confidence: 99%
“…Even worse failure rate was reported in another study on engineering university students' difficulties in solving a problem from calculus that had a "non-routine" wording [9]. About 95% of the students (187 out of 197) failed to solve an application problem on a test mainly due to the unusual for them wording of the problem: instead of the more common formulation "find the velocity that minimizes the total cost of a journey" the question was "show that to minimize the total cost of a journey the truck should run approximately 28 km/h".…”
mentioning
confidence: 96%
“…Difficulties with mathematics are also experienced by university students. A study of Klymchuk, Zverkova, Gruenwald, and Sauerbier (2010) revealed that many university students could not construct a simple function that representing a familiar context. A general perspective on students' difficulties in mathematics is given by Russell, O'Dwyer, and Miranda (2009) who found that students' difficulties in mastering concept occur are caused by students' inability to link between the knowledge that they are studying and the prior knowledge they have.…”
mentioning
confidence: 99%